A Revised Version of Ant Colony Algorithm for One-Dimensional Cutting Stock Problem - Eshghi, Kourosh; Javanshir, Hasan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The one-dimensional cutting stock problem has many applications in industries and during the past few years has been one of the centers of attention among the researchers in the field of applied operations research. In this paper, a revised version of Ant Colony Optimization (ACO) technique is presented to solve this problem. This paper is a sequel to the previous ACO algorithm presented by the authors. In this algorithm, according to some probabilistic rules, artificial ants will select cutting patterns and generate a feasible solution. Computational results show the high efficiency and accuracy of the proposed algorithm for solving one- dimensional cutting stock problem.